24‐3: Invited Paper: Light Out‐Coupling of OLEDs: the Transparent Electrode Effects. Issue 1 (May 2016) - Wu, Chung‐Chih; Huang, Yi‐Hsiang; Chen, Chien‐Yu; Lee, Wei‐Kai; Lu, Chun‐Yang; Chen, Yi‐Jiun; Lin, Hoang Yan
Abstract : Judicious use of low‐index transparent conductors in transparent electrodes of OLEDs effectively enhances out‐coupling both into substrate and directly into air. 39%, 57%, and 62% EQEs have been demonstrated for OLEDs with simple planar structures, planar transparent electrode plus external extraction, and nanostructured composite transparent electrode plus external extraction, respectively.